2022
DOI: 10.3389/fnut.2022.890640
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Grape Juice to Develop New Isotonic Drinks With Antioxidant Capacity and Interesting Sensory Properties

Abstract: Nowadays, the sector of isotonic beverages has developed its market based on fruit juices that provide a sports drink with antioxidant and biological activities in addition to their principal role of rehydration and replacement of minerals and carbohydrates during physical exercise. Consumption of grape juice is increasing worldwide because of its sensory characteristics and nutritional value. It contains mainly water, sugars, organic acids, and phenolic compounds. Phenolic compounds play a major role in preve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 78 publications
0
1
0
Order By: Relevance
“…The results of TPI (Table 3) and antioxidant activity evaluation (Figure 3) demonstrate that the prepared beverages presented a good source of phenolic content and antioxidant capacity. Furthermore, we previously demonstrated [53] the contribution of grape juice to isotonic beverages, citing different studies that demonstrated the positive effect of grape juice consumption during physical activities, which improves antioxidant activity and performance, protects against oxidative damage, and reduces inflammation [14,[54][55][56][57][58][59][60]. Accordingly, it is known that herbs and spices have excellent antioxidant activity.…”
Section: Discussionmentioning
confidence: 99%
“…The results of TPI (Table 3) and antioxidant activity evaluation (Figure 3) demonstrate that the prepared beverages presented a good source of phenolic content and antioxidant capacity. Furthermore, we previously demonstrated [53] the contribution of grape juice to isotonic beverages, citing different studies that demonstrated the positive effect of grape juice consumption during physical activities, which improves antioxidant activity and performance, protects against oxidative damage, and reduces inflammation [14,[54][55][56][57][58][59][60]. Accordingly, it is known that herbs and spices have excellent antioxidant activity.…”
Section: Discussionmentioning
confidence: 99%
“…Studies found that consumers appreciate grape products whose sensory attributes are perceived at a high intensity and balance each other [40]. According to Bendaali et al [41], color is the most important characteristic when choosing beverages and is used by consumers as an indicator of juice quality. There is a strong relationship between color and flavor, as consumers can base their expectation of flavor on the color of products [42].…”
Section: Ideal Productmentioning
confidence: 99%
“…Color is one of the important indicators when choosing drinks, which can not only reflect the quality of fruit but also make a certain contribution to the commercial value of fruit juice [39]. Many consumers expect flavor through the color of food, as an indicator of juice quality for selection [40]. The CIELAB color space is widely used to measure the overall color changes during juice processing and storage [41], as shown in Figure 5.…”
Section: Color Analysismentioning
confidence: 99%